Investigation on Beam Expansion Method for Weakly-Coupled FMF Connections - Ruiting Cheng; Yu Yang; Jiarui Zhang; Mingqing Zuo; Shuailuo Huang; Yuyang Gao; Zhangyuan Chen; Yongqi He; Juhao Li (IEEE Photonics Journal)
Recently, weakly-coupled mode-division multiplexing (MDM) technology based on few-mode fibers (FMFs) has been widely investigated as a promising candidate for capacity enhancement of various applications such as optical interconnections. However, non-ideal FMF connections may break the weakly-coupled condition and be a great challenge for practical applications. Previous studies have shown that beam expansion methods may be effective for coupling loss suppression at non-ideal single-mode connections, but their effectiveness has seldom been discussed for non-ideal FMF connections as far as we know. In this article, we firstly investigate two typical beam expansion methods for the suppression of modal crosstalk and coupling loss induced by fiber misalignment or air gap at FMF connections by simulations, and the simulation results show that not all the methods are effective. The Dolph-Chebychev (DC) taper method could achieve significant performance improvement, while the gradient-index (GRIN) lens method may even degrade the performance of FMF connections. Then the beam expansion method is experimentally verified utilizing tapered two-mode fiber (TMF) connectors, which are fabricated with thermally-expanded-core (TEC) processing. The measurement results show that compared with the untapered case, the tapered TMF connectors show higher tolerance to misalignment and can achieve no less than 7.7 dB crosstalk reduction and 0.65 dB loss reduction when the misalignment at the connection is 2 μm. This work is beneficial to the application of weakly-coupled MDM systems.